The Evaluation of Alleged Defamation: A Forensic Linguistics Analysis - Vidhiasi, Dhion Meitreya; Saifullah, Aceng Ruhendi; Bachari, Andika Dutha (LP2M IAIN Sultan Amai Gorontalo, 2023)
Defamation remains a prevalent occurrence on a global scale. In Indonesia, the fervor surrounding the outcomes of the 2014 presidential election contestation has led to a noticeable escalation in the level of fanaticism among supporters of the respective presidential and vice-presidential candidates. Frequently, the act of posting tweets on the social media platform Twitter can result in the author becoming entangled in a legal dispute pertaining to defamation. The objective of this research is to investigate the potential occurrence of defamation committed by Natalius Pigai, the former National Human Rights Commission (Komnas HAM) member. The analytical framework employed in this study to assess the linguistic techniques employed in the data, with the aim of identifying potential instances of defamation, was Appraisal Theory as proposed by Martin and White (2005). The data was extracted from a Twitter post authored by Natalius Pigai (@NataliusPigai2) on October 1, 2021. The findings indicated that Jokowi and Ganjar were subjected to poor evaluation in relation to their treatment of the Papuan population. The presence of this adverse evaluation also gives rise to the possibility of defamation in accordance with the provisions outlined in the Criminal Code and the ITE Law. The presence of credible factual evidence supports the assertion that Natalius Pigai's tweet can be classified as hate speech, which has the potential to result in defamation. The findings derived from this study could potentially facilitate the application of law enforcement strategies in the Indonesian police investigation, as well as in other nations that are undertaking comparable reforms to those observed in Indonesia.